PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN EFIKASI DIRI TERHADAP MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN FKIP UNS - Azis Rahmat Hidayat; Patni Ninghardjanti; Susantiningrum Susantiningrum (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
The aims of the study are to determine: (1) the effect of entrepreneurial knowledge on interest in entrepreneurship (2) the effect of self-efficacy on interest in entrepreneurship (3) the influence of entrepreneurial knowledge and self-efficacy on interest in entrepreneurship. The research used quantitative proportional random sampling method with a total of 60 from 148 populations. Data collection by questionnaire. Analysis using multiple linear regression technique with analysis prerequisite test: normality test, linearity test and multicollinearity test. The results of the study: (1) there is a significant effect of entrepreneurial knowledge on entrepreneurial interest tcount is greater than the results of the t-test analysis obtained by the value of tcount (2.397)> ttable (1.984) the significance value is less than 0.10 (0.000 <0.10); (2) there is a significant effect of self-efficacy on students' interest in entrepreneurship, tcount is greater than the results of the t-test analysis, it is obtained that tcount (2.520) > ttable (1.984) the significance value is less than 0.10 (0.006 <0.10); (3) there is an influence of entrepreneurial knowledge and self-efficacy on interest in entrepreneurship. Fcount is greater than the value of Ftable (Fcount > Ftable, which is 11.988 > 3.92), the significance value is less than 0.10 (0.000 < 0.10) . The entrepreneurial knowledge variable gave an effective contribution of 13.70% and a relative contribution of 48.22%, while the self-efficacy variable gave an effective contribution of 14.67% and a relative contribution of 51.6%